1. А) ![\lg (x^{2} - 2x) - \lg (2x + 12) = 0 \lg (x^{2} - 2x) - \lg (2x + 12) = 0](https://tex.z-dn.net/?f=%5Clg%20%28x%5E%7B2%7D%20-%202x%29%20-%20%5Clg%20%282x%20%2B%2012%29%20%3D%200)
ОДЗ:
0} \atop \bigg{2x + 12 > 0}} \right. \ \ \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x \in (-\infty; 0)\cup(2; +\infty)} \atop \bigg{x \in (-6; +\infty) \ \ \ \ \ \ \ \ \ \ \ }} \right. \ \ \ \ \ \ \ \ x \in (-6; 0) \cup (2; +\infty)" alt="\left \{ {\bigg{x^{2} - 2x > 0} \atop \bigg{2x + 12 > 0}} \right. \ \ \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x \in (-\infty; 0)\cup(2; +\infty)} \atop \bigg{x \in (-6; +\infty) \ \ \ \ \ \ \ \ \ \ \ }} \right. \ \ \ \ \ \ \ \ x \in (-6; 0) \cup (2; +\infty)" align="absmiddle" class="latex-formula">
![\lg (x^{2} - 2x) = \lg (2x + 12) \\x^{2} - 2x = 2x + 12\\x^{2} - 4x - 12 = 0\\x_{1} = -2; \ x_{2} = 6 \lg (x^{2} - 2x) = \lg (2x + 12) \\x^{2} - 2x = 2x + 12\\x^{2} - 4x - 12 = 0\\x_{1} = -2; \ x_{2} = 6](https://tex.z-dn.net/?f=%5Clg%20%28x%5E%7B2%7D%20-%202x%29%20%3D%20%5Clg%20%282x%20%2B%2012%29%20%5C%5Cx%5E%7B2%7D%20-%202x%20%3D%202x%20%2B%2012%5C%5Cx%5E%7B2%7D%20-%204x%20-%2012%20%3D%200%5C%5Cx_%7B1%7D%20%3D%20-2%3B%20%5C%20x_%7B2%7D%20%3D%206)
Ответ: ![x_{1} = -2; \ x_{2} = 6 x_{1} = -2; \ x_{2} = 6](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%20-2%3B%20%5C%20x_%7B2%7D%20%3D%206)
Б) ![\log_{2}(x+1) - \log_{2}(x-1) = 1 \log_{2}(x+1) - \log_{2}(x-1) = 1](https://tex.z-dn.net/?f=%5Clog_%7B2%7D%28x%2B1%29%20-%20%5Clog_%7B2%7D%28x-1%29%20%3D%201)
ОДЗ:
0} \atop \bigg{x-1 > 0}} \right. \ \ \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x \in (-1; +\infty)} \atop \bigg{x \in (1; +\infty) \ \ }} \right. \ \ \ \ \ \ \ \ x \in (1; +\infty)" alt="\left \{ {\bigg{x+1 > 0} \atop \bigg{x-1 > 0}} \right. \ \ \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x \in (-1; +\infty)} \atop \bigg{x \in (1; +\infty) \ \ }} \right. \ \ \ \ \ \ \ \ x \in (1; +\infty)" align="absmiddle" class="latex-formula">
![\log_{2}(x+1) = \log_{2}2 + \log_{2}(x-1)\\\log_{2}(x+1) = \log_{2}2(x-1)\\x + 1 = 2(x-1)\\x + 1 = 2x - 2\\x = 3 \log_{2}(x+1) = \log_{2}2 + \log_{2}(x-1)\\\log_{2}(x+1) = \log_{2}2(x-1)\\x + 1 = 2(x-1)\\x + 1 = 2x - 2\\x = 3](https://tex.z-dn.net/?f=%5Clog_%7B2%7D%28x%2B1%29%20%3D%20%5Clog_%7B2%7D2%20%2B%20%5Clog_%7B2%7D%28x-1%29%5C%5C%5Clog_%7B2%7D%28x%2B1%29%20%3D%20%5Clog_%7B2%7D2%28x-1%29%5C%5Cx%20%2B%201%20%3D%202%28x-1%29%5C%5Cx%20%2B%201%20%3D%202x%20-%202%5C%5Cx%20%3D%203)
Ответ: ![x = 3 x = 3](https://tex.z-dn.net/?f=x%20%3D%203)
В) ![2\log_{4}^{2}x + 5\log_{4}x - 3 = 0 2\log_{4}^{2}x + 5\log_{4}x - 3 = 0](https://tex.z-dn.net/?f=2%5Clog_%7B4%7D%5E%7B2%7Dx%20%2B%205%5Clog_%7B4%7Dx%20-%203%20%3D%200)
ОДЗ:
0; \ x \in (0; + \infty)" alt="x > 0; \ x \in (0; + \infty)" align="absmiddle" class="latex-formula">
Замена: ![\log_{4}x = t \log_{4}x = t](https://tex.z-dn.net/?f=%5Clog_%7B4%7Dx%20%3D%20t)
![2t^{2} + 5t - 3 = 0\\D = 25 + 24 = 49\\\\t_{1,2} = \dfrac{-5 \pm 7}{4} = \left[\begin{array}{ccc}t_{1} = -3 \\t_{2} = \dfrac{1}{2} \end{array}\right 2t^{2} + 5t - 3 = 0\\D = 25 + 24 = 49\\\\t_{1,2} = \dfrac{-5 \pm 7}{4} = \left[\begin{array}{ccc}t_{1} = -3 \\t_{2} = \dfrac{1}{2} \end{array}\right](https://tex.z-dn.net/?f=2t%5E%7B2%7D%20%2B%205t%20-%203%20%3D%200%5C%5CD%20%3D%2025%20%2B%2024%20%3D%2049%5C%5C%5C%5Ct_%7B1%2C2%7D%20%3D%20%5Cdfrac%7B-5%20%5Cpm%207%7D%7B4%7D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dt_%7B1%7D%20%3D%20-3%20%5C%5Ct_%7B2%7D%20%3D%20%5Cdfrac%7B1%7D%7B2%7D%20%5Cend%7Barray%7D%5Cright)
![1) \ \log_{4}x = -3; \ x = 4^{-3} = \dfrac{1}{64} \\2) \ \log_{4}x = \dfrac{1}{2}; \ x = \sqrt{4} = 2 1) \ \log_{4}x = -3; \ x = 4^{-3} = \dfrac{1}{64} \\2) \ \log_{4}x = \dfrac{1}{2}; \ x = \sqrt{4} = 2](https://tex.z-dn.net/?f=1%29%20%5C%20%5Clog_%7B4%7Dx%20%3D%20-3%3B%20%5C%20x%20%3D%204%5E%7B-3%7D%20%3D%20%5Cdfrac%7B1%7D%7B64%7D%20%5C%5C2%29%20%5C%20%5Clog_%7B4%7Dx%20%3D%20%5Cdfrac%7B1%7D%7B2%7D%3B%20%5C%20x%20%3D%20%5Csqrt%7B4%7D%20%3D%202)
Ответ: ![x_{1} = \dfrac{1}{64}; \ x_{2} = 2 x_{1} = \dfrac{1}{64}; \ x_{2} = 2](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%20%5Cdfrac%7B1%7D%7B64%7D%3B%20%5C%20x_%7B2%7D%20%3D%202)
Г) ![x^{\log _{0,5}(x)-1} = \dfrac{1}{64} x^{\log _{0,5}(x)-1} = \dfrac{1}{64}](https://tex.z-dn.net/?f=x%5E%7B%5Clog%20_%7B0%2C5%7D%28x%29-1%7D%20%3D%20%5Cdfrac%7B1%7D%7B64%7D)
ОДЗ:
0; \ x \in (0; + \infty)" alt="x > 0; \ x \in (0; + \infty)" align="absmiddle" class="latex-formula">
![\log _{0,5}x^{\log _{0,5}(x)-1} = \log _{0,5}\bigg(\dfrac{1}{64}\bigg)\\(\log _{0,5}(x)-1) \ \cdotp \log _{0,5}x = 6\\\log_{0,5}^{2}x - \log _{0,5}x - 6 = 0 \log _{0,5}x^{\log _{0,5}(x)-1} = \log _{0,5}\bigg(\dfrac{1}{64}\bigg)\\(\log _{0,5}(x)-1) \ \cdotp \log _{0,5}x = 6\\\log_{0,5}^{2}x - \log _{0,5}x - 6 = 0](https://tex.z-dn.net/?f=%5Clog%20_%7B0%2C5%7Dx%5E%7B%5Clog%20_%7B0%2C5%7D%28x%29-1%7D%20%3D%20%5Clog%20_%7B0%2C5%7D%5Cbigg%28%5Cdfrac%7B1%7D%7B64%7D%5Cbigg%29%5C%5C%28%5Clog%20_%7B0%2C5%7D%28x%29-1%29%20%5C%20%5Ccdotp%20%5Clog%20_%7B0%2C5%7Dx%20%3D%206%5C%5C%5Clog_%7B0%2C5%7D%5E%7B2%7Dx%20-%20%5Clog%20_%7B0%2C5%7Dx%20-%206%20%3D%200)
Замена: ![\log _{0,5}x = t \log _{0,5}x = t](https://tex.z-dn.net/?f=%5Clog%20_%7B0%2C5%7Dx%20%3D%20t)
![t^{2} - t - 6 = 0; \\t_{1} = -2; \ t_{2} = 3 t^{2} - t - 6 = 0; \\t_{1} = -2; \ t_{2} = 3](https://tex.z-dn.net/?f=t%5E%7B2%7D%20-%20t%20-%206%20%3D%200%3B%20%5C%5Ct_%7B1%7D%20%3D%20-2%3B%20%5C%20t_%7B2%7D%20%3D%203)
![1) \ \log _{0,5}x = -2; \ x = 0,5^{-2} = 4\\2) \ \log _{0,5}x =3; \ x = 0,5^{3} = 0,125 1) \ \log _{0,5}x = -2; \ x = 0,5^{-2} = 4\\2) \ \log _{0,5}x =3; \ x = 0,5^{3} = 0,125](https://tex.z-dn.net/?f=1%29%20%5C%20%5Clog%20_%7B0%2C5%7Dx%20%3D%20-2%3B%20%5C%20x%20%3D%200%2C5%5E%7B-2%7D%20%3D%204%5C%5C2%29%20%5C%20%5Clog%20_%7B0%2C5%7Dx%20%3D3%3B%20%5C%20x%20%3D%200%2C5%5E%7B3%7D%20%3D%200%2C125)
Ответ: ![x = 0,125; \ x = 4 x = 0,125; \ x = 4](https://tex.z-dn.net/?f=x%20%3D%200%2C125%3B%20%5C%20x%20%3D%204)
2. ![\left \{ {\bigg{\log_{2}(x^{2} + 4xy + 4y^{2}) = 4} \atop \bigg{\log_{2}x=\log_{2}(2y - 4) \ \ \ \ \ }} \right. \ \ \ \ \ \ \ \ \left \{ {\bigg{\log_{2}(x+2y)^{2} = 4} \atop \bigg{x=2y - 4 \ \ \ \ \ \ \ \ \ }} \right. \left \{ {\bigg{\log_{2}(x^{2} + 4xy + 4y^{2}) = 4} \atop \bigg{\log_{2}x=\log_{2}(2y - 4) \ \ \ \ \ }} \right. \ \ \ \ \ \ \ \ \left \{ {\bigg{\log_{2}(x+2y)^{2} = 4} \atop \bigg{x=2y - 4 \ \ \ \ \ \ \ \ \ }} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%5Cbigg%7B%5Clog_%7B2%7D%28x%5E%7B2%7D%20%2B%204xy%20%2B%204y%5E%7B2%7D%29%20%3D%204%7D%20%5Catop%20%5Cbigg%7B%5Clog_%7B2%7Dx%3D%5Clog_%7B2%7D%282y%20-%204%29%20%5C%20%5C%20%5C%20%5C%20%5C%20%7D%7D%20%5Cright.%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5Cleft%20%5C%7B%20%7B%5Cbigg%7B%5Clog_%7B2%7D%28x%2B2y%29%5E%7B2%7D%20%3D%204%7D%20%5Catop%20%5Cbigg%7Bx%3D2y%20-%204%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%7D%7D%20%5Cright.)
![\left \{ {\bigg{\log_{2}(x+2y) = 2} \atop \bigg{x=2y - 4 \ \ \ \ \ \ \ }} \right.\\\log_{2}(2y - 4+2y) = 2\\\log_{2}(4y - 4) = \log_{2}4\\4y - 4 = 4\\4y = 8\\y = 2\\x=2 \ \cdotp 2 - 4 = 0 \left \{ {\bigg{\log_{2}(x+2y) = 2} \atop \bigg{x=2y - 4 \ \ \ \ \ \ \ }} \right.\\\log_{2}(2y - 4+2y) = 2\\\log_{2}(4y - 4) = \log_{2}4\\4y - 4 = 4\\4y = 8\\y = 2\\x=2 \ \cdotp 2 - 4 = 0](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%5Cbigg%7B%5Clog_%7B2%7D%28x%2B2y%29%20%3D%202%7D%20%5Catop%20%5Cbigg%7Bx%3D2y%20-%204%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%7D%7D%20%5Cright.%5C%5C%5Clog_%7B2%7D%282y%20-%204%2B2y%29%20%3D%202%5C%5C%5Clog_%7B2%7D%284y%20-%204%29%20%3D%20%5Clog_%7B2%7D4%5C%5C4y%20-%204%20%3D%204%5C%5C4y%20%3D%208%5C%5Cy%20%3D%202%5C%5Cx%3D2%20%5C%20%5Ccdotp%202%20-%204%20%3D%200)
Ответ: ![(0; 2) (0; 2)](https://tex.z-dn.net/?f=%280%3B%202%29)